Francisco Zúñiga Díaz on the image in literary ateliers - Castro Carvajal, Hiram (2018)
From the idea of “Lezamian image”- José Lezama Lima (Cuba)-, the author analyzes the poetic work of Francisco Zúñiga Díaz, a Costa Rican contemporary writer who promoted poetic creation among young people through his literary ateliers in San Joseé, Costa Rica.